Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Simulated freeze–thaw cycles restructure plastisphere microbiomes and functional gene co-occurrence networks in alpine lake sediment microcosms - Li Naying; Zhong Bo; Wu Wei-Min; Liu Xin; Liu Ruixi; Mei Xintong; Wang Xiaofeng; Zhou Li; Yi Shaoliang; Lin Honghui; He Yixin (Environmental Pollution, 2026)

In situ trophic modes and metabolic traits of the dinoflagellate Karenia in response to short-term localized warming - Hao Zhang; Xiao Ma; Shufei Zhang; Lingshuai Zhang; Chenhui Xiang; Zhiqin Wang; Lin Zhu; Bowei Gu; Xingyu Song; Honghui Huang; Lijuan Long; Xiaomin Xia (Marine Pollution Bulletin, 2026)

Microplastic pollution enhances methane emissions from remote mountainous lakes via plastisphere-mediated microbial processes - Naying Li; Bo Zhong; Wei-Min Wu; Xintong Mei; Ruixi Liu; Xin Liu; Xianxiang Li; Rehman Abdul; Shaoliang Yi; Li Zhou; Honghui Lin; Xiaofeng Wang; et al. (Journal of Environmental Sciences, 2026)

Treatment of Kiwifruit with Bacillus subtilis LS11 postharvest mitigates disease occurrence and alters its microbiome - Huiyun Song; Zhihao Duan; Jian Yang; BeiBei Liang; Honghui Shi; Xiaoling Wang; Zhu Gao; Liuyi Pan; Jipeng Mao; Xuchen Gong; Dongliang Yao; Mengfei Lin (Postharvest Biology and Technology, 2026)

Microencapsulation mechanism of menthol and menthone by hydroxypropyl-β-cyclodextrin for enhanced stability and prolonged retention - Honghui Guo; Haohong Yao; Quanxing Zheng; Quanling Xie; Hongliang Lu; Xiaohua Deng; Yan Lin; Ming’en Zhang; Pengfei Ma; Zhuan Hong; Xiaoqing Huang (Food and Bioproducts Processing, 2026)

Freeze–thaw cycles restructure PET microplastics in sediments into new habitat of microbial carbon metabolism - Naying Li; Bo Zhong; Xin Liu; Wei-Min Wu; Xintong Mei; Ruixi Liu; Li Zhou; Honghui Lin; Shaoliang Yi; Yixin He (Chemical Engineering Journal, 2026)

Nanoscale zero-valent iron mediates Fe speciation-microbe synergism for simultaneous remediation of 2,3′,4,4′,5-pentachlorobiphenyl and Cd co-contaminated soil and safe rice production - Yangzhi Liu; Jinchuan Ma; Chenghu Yang; Jing Zhang; Honghui Wang; Qilu Cheng; Yingxia Liu; Qiang Wang; Hui Lin; Junwei Ma (Journal of Hazardous Materials, 2026)

Soil bacteria predominantly drive ecosystem multifunctionality within disturbed meadows on the Tibetan Plateau - Long Huang; Dandan Wei; Weikai Bao; Bin Hu; Honghui Lin; Fanglan Li (Applied Soil Ecology, 2026)

Micro-ecosystem of plastisphere in high-altitude lake: Hotspots of anaerobic carbon cycle distinct from sediments - Naying Li; Bo Zhong; Xin Liu; Wei-Min Wu; Xintong Mei; Zao Yang; Abdul Rehman; Li Zhou; Honghui Lin; Yixin He (Journal of Hazardous Materials, 2025)

Integrated metabolomics and transcriptomics reveal the nutritional profiles and molecular mechanisms in colored cauliflowers - Xiaoguang Sheng; Mengfei Song; Jiansheng Wang; Huifang Yu; Yusen Shen; Shuting Qiao; Fan Lin; Sifan Du; Honghui Gu (Food Bioscience, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Humic acid-supported nanoscale zero-valent iron for sustainable cadmium remediation and crop safety in farmland soil - Yangzhi Liu; Dongren Zhou; Peng Huang; Chenghu Yang; Jing Zhang; Honghui Wang; Qilu Cheng; Yingxia Liu; Chengxiang Gao; Jinchuan Ma; Hui Lin; Junwei Ma (Journal of Hazardous Materials, 2025)

Potential ecological risk of microplastics contamination to environment in protect area lakes - Li Naying; Mei Xintong; Zhong Bo; Wang Xiaofeng; Liu Xin; Yang zao; Lin Honghui; He Yixin (Journal of Hazardous Materials, 2025)

Comprehensive analysis reveals the prognostic and immunological role of PSMD13 in hepatocellular carcinoma - Yun Li; Honghui Liu; Na Liu; Lin Chen; Ruijie Liu (Mammalian Genome, 2025)

Comprehensive suitability assessment of fish habitat by integrating mechanism model and bayesian network model - Yuliang Yuan; Ran Li; Jingjie Feng; Hang Wan; Honghui Lin; Xiaolong Cheng (Ecological Engineering, 2025)

DNA Barcodes for Identifying Fish Egg Species Diversity in Summer and Autumn in the Southwest Daya Bay, China - Shile Zheng; Jianbin Lin; Fengxia Wu; Yiyong Rao; Jinrun Wang; Siyuan He; Honghui Huang; Gang Hou (Fishes, 2024)
Identifying fish eggs and understanding fish reproductive periods are necessary for informed fishery management. However, accurate the identification of fish eggs is difficult because eggs have few distinct characters, and their morphology varies ontogenetically. Using cytochrome c oxidase subunit I, we identified fish eggs from ichthyoplankton samples collected in the summer and autumn of 2021 from southwestern Daya Bay, China. Of 567 fish eggs, 498 high-quality cytochrome c oxidase subunit I sequences were obtained, of which 116 eggs (23.3%) could be identified to species; 364 (73.1%) to genus, family and/or order; and 18 (3.6%) could not be assigned. Of 51 apparent taxa, 46 were identified to 6 orders, 19 families, and 30 genera; 20 to the species and 25 to the genus and/or family, and 1 to the order. Among these 51 taxa, 35 occurred in summer, 29 occurred in autumn, and 13 occurred in both seasons; 22 occurred only in summer and 16 only in autumn, indicating species-specific spawning periods. High-resolution photographs of eggs are provided to facilitate subsequent identification based on morphology. These results will facilitate the identification of spawning grounds and their protection, to more holistically manage fishery resources in Daya Bay, China.

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

Relationship between photochromism and persistent luminescence in barium-magnesium silicates - Rujun Yang; Long Chen; Cunjian Lin; Honghui Huang; Zishuang Wu; Chenhan Zhan; Yixi Zhuang; Rong-Jun Xie (Chemical Engineering Journal, 2024)

Anthropogenic and biological activities elevate microplastics pollution in headwater ecosystem of Yangtze tributaries in Hindu Kush-Himalayan region - Naying Li; Xiaofeng Wang; Xianxiang Li; Shaoliang Yi; Yun Guo; Ning Wu; Honghui Lin; Bo Zhong; Wei-Min Wu; Yixin He (Journal of Hazardous Materials, 2024)

Postharvest treatment with Bacillus velezensis LX mitigates disease incidence and alters the microbiome on kiwifruit surface - Zhihao duan; Huiyun Song; Honghui Shi; Zhu Gao; Jipeng Mao; Yunpeng Cao; Heqiang Huo; Juncheng Li; Xiaoling Wang; Mengfei Lin (Postharvest Biology and Technology, 2024)

Field investigation on the change process of microbial community structure in large-deep reservoir during the initial impoundment - Sizhen Liang; Fangbo Zhang; Ran Li; Hailong Sun; Jingjie Feng; Zhuo Chen; Honghui Lin (Journal of Environmental Management, 2023)

Vocalization Behavior of Chinese Bahaba (Bahaba taipingensis) during the Reproduction Season - Hongquan Li; Zhongchang Song; Jiangang Hui; Yingnan Su; Weijie Fu; Shufei Zhang; Lin Yan; Kuoqiu Yan; Honghui Huang; Yu Zhang (Journal of Marine Science and Engineering, 2023)
Chinese bahaba (Bahaba taipingensis) is a critically endangered fish species, which can produce sounds like other Sciaenidae species. In this study, sounds produced by sexually mature Chinese bahaba were recorded during the reproduction season for the first time. Two distinct types of sounds were observed during the reproduction season, termed as single drum and fast drum trains calls. Single drum callings occurred as a series of trains with rapid pulses, while fast drum trains callings were mainly made of a single signal. The single drum and fast drum trains had a peak frequency of 77.8 ± 16.2 Hz and 79.1 ± 8.7 Hz, respectively. Statistical analysis suggested significant differences in −3 dB bandwidth, signal duration, and root-mean-square sound pressure levels, except for peak frequency (p

Mitochondrial alternative oxidase enhanced ABA-mediated drought tolerance in Solanum lycopersicum - Kang Qiao; Xiuhong Yao; Zuxu Zhou; Jiawei Xiong; Ke Fang; Jiayi Lan; Fei Xu; Xingguang Deng; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2023)

Protein kinase PpCIPK1 modulates plant salt tolerance in Physcomitrella patens - Fei Xiao; Xiaochuan Li; Jiaxian He; Jinfeng Zhao; Guochun Wu; Qianyuan Gong; Huapeng Zhou; Honghui Lin (Plant Molecular Biology, 2021)

A gain-of-function mutation in Brassinosteroid-insensitive 2 alters Arabidopsis floral organ development by altering auxin levels - Taotao Li; Xinke Kang; Lin Wei; Dawei Zhang; Honghui Lin (Plant Cell Reports, 2020)

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

NAP is involved in GA-mediated chlorophyll degradation and leaf senescence by interacting with DELLAs in Arabidopsis - Wei Lei; Yan Li; Xiuhong Yao; Kang Qiao; Lin Wei; Baohui Liu; Dawei Zhang; Honghui Lin (Plant Cell Reports, 2020)

Occurrence of cucumber mosaic virus subgroup II and its genetic diversity in Sichuan, southwest of China - Chunyan Fei; Zhenpeng Xu; Lijuan Chen; Wenshan Zou; Rui Lv; Honghui Lin; Dehui Xi (Journal of Plant Pathology, 2018)

Correction to: Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbing Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)

Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbin Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)

A CRISPR/Cas9 toolkit for efficient targeted base editing to induce genetic variations in rice - Bin Ren; Fang Yan; Yongjie Kuang; Na Li; Dawei Zhang; Honghui Lin; Huanbin Zhou (Science China Life Sciences, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Temperature dependent defence of Nicotiana tabacum against Cucumber mosaic virus and recovery occurs with the formation of dark green islands - Feifei Zhao; Yanan Li; Lijuan Chen; Lisha Zhu; Han Ren; Honghui Lin; Dehui Xi (Journal of Plant Biology, 2016)

The roles of autophagy in development and stress responses in Arabidopsis thaliana - Xin Lv; Xiaojun Pu; Gongwei Qin; Tong Zhu; Honghui Lin (Apoptosis, 2014)

Prokaryotic expression of pathogenesis related protein 1 gene from Nicotiana benthamiana: antifungal activity and preparation of its polyclonal antibody - Feng Zhu; Moyun Xu; Shaodong Wang; Shudan Jia; Ping Zhang; Honghui Lin; Dehui Xi (Biotechnology Letters, 2012)

BAK1 and BKK1 in Arabidopsis thaliana confer reduced susceptibility to turnip crinkle virus - Hui Yang; Xiaoping Gou; Kai He; Dehui Xi; Junbo Du; Honghui Lin; Jia Li (European Journal of Plant Pathology, 2010)